The selection of food shopping locations by UK suburban households: A multivariate analysis - A. R. Yates; K. A. Yeomans (South African Journal of Business Management, 1985)
In this article a behavioural model of retail location is discussed which differs from established models in two respects. Firstly, in the behavioural model the demand for retail outlets is emphasized rather than the supply of retail outlets. Secondly, psychological and sociological constructs are used to help explain store selection behaviour. The behavioural model differs from established location theory in that an attempt is made to study the act of shopping in relation to other human activities. The basic postulate of the model is that people are constrained in their shopping behaviour. People can then be rated on a scale of constraints, which can be used to predict store selection behaviour.